Covered self-expandable metallic stents versus plastic stents for endoscopic ultrasound-guided hepaticogastrostomy in patients with malignant biliary obstruction - Taro Shibuki; Kei Okumura; Masanari Sekine; Ikuhiro Kobori; Aki Miyagaki; Yoshihiro Sasaki; Yuichi Takano; Yusuke Hashimoto (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims Covered self-expandable metallic stents (cSEMS) have become popular for endoscopic ultrasound-guided hepaticogastrostomy with transmural stenting (EUS-HGS). We compared the time to recurrent biliary obstruction (TRBO), complications, and reintervention rates between EUS-HGS using plastic stent (PS) and cSEMS in patients with unresectable malignancies at multicenter institutions in Japan. Methods Patients with unresectable malignant biliary obstruction who underwent EUS-HGS between April 2015 and July 2020 at any of the six participating facilities were enrolled. Primary endpoint: TRBO; secondary endpoints: rate of complications other than recurrent biliary obstruction and technical success rate of reintervention were evaluated. Results PS and cSEMS were used for EUS-HGS in 109 and 43 patients, respectively. The TRBO was significantly longer in the cSEMS group than in the PS group (646 vs. 202 days). Multivariate analysis identified two independent factors associated with a favorable TRBO: combined EUS-guided antegrade stenting with EUS-HGS and the use of cSEMS. No significant difference was observed in the rate of complications other than recurrent biliary obstruction between the two groups. The technical success rate of reintervention was 85.7% for PS and 100% for cSEMS (p=0.309). Conclusions cSEMS might be a better option for EUS-HGS in patients with unresectable malignancies, given the longer TRBO.